Role of School Administration in Activating the Familial ‎Partnership in Light of Epstein Model - Al-Balawi , Khaleel; Abu Masha'al, Kholoud (Jordan Journal of Educational Sciences, 2021)
This study aimed at identifying the role of school administration in activating the familial partnership in light of Epstein Model. The study applied the descriptive method and the sample comprised (127) male and female school principals in Zarqa, Directorate of Edcuation/1, Jordan. To achieve the study aim, the researchers constructed a questionnaire with reliance on Epstein Model.The questionnaire included six domains: parenting, communication, volunteering, home learning, decision taking and cooperation with the community.The results showed that male and female school principals of Zarqa Directorate of Education/1 practice all familial partnership domains at a "medium" level. Moreover, the results did not show statistically significant differences in school principals' practices of familial partnership in Zarqa Directorate of Education/1, which could be attributed to gender or years of experience variables